LEARNING METHOD OF EMOTIONAL DEMONSTRATION FOR IMPROVING TEENAGERS’ SMOKING HAZARD INFORMATION LITERACY - Arif, Ulfatu; Nurhayati, Sri; Ahsan, Md Hafizi (Universitas Muhammadiyah Mataram, 2024)
Abstrak: Tujuan dari penelitian ini adalah untuk menganalisis pengaruh penyuluhan bahaya merokok dengan metode Emo Demo pada anak usia remaja. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan desain penelitian pre eksperimental One Group Pretest Postest Design dengan jumlah subjek penelitian sebanyak 20 orang. Penelitian dilaksanakan di SMPN 3 Sindangkerta Kabupaten Bandung Barat. Variabel yang akan diteliti meliputi pengetahuan dan sikap merokok yang diukur dengan menggunakan instrumen pengetahuan pretest dan posttest, lembar observasi perilaku, dan media penyuluhan dengan metode Emo Demo. Teknik analisi data menggunakan software statistic SPSS. Hasil pengolahan data pengaruh penyuluhan bahaya rokok dengan menggunakan metode emo-demo terhadap pengetahuan didapatkan diketahui nilai Sig (2-tailed) sebesar 0,000, maka dapat disimpulkan bahwa pengetahuan remaja setelah mendapatkan penyuluhan dengan metode emo demo lebih baik daripada sebelum mendapatkan penyuluhan emo-demo. Begitu juga pengaruh penyuluhan bahaya rokok menggunakan metode emo-demo terhadap perubahan sikap terhadap perilaku merokok didapatkan Asymp Sig (2-tailed) sebesar 0,000 < 0,05, hal ini menunjukkan bahwa terdapat perbedaan sikap terhadap perilaku merokok setelah penyuluhan bahaya merokok dengan menggunakan metode emo-demo dengan sebelum. Dengan demikian dapat disimpulkan bahwa penyuluhan dengan menggunakan metode emo-demo mengenai dampak bahaya merokok efektif meningkatkan sikap dan pengetahuan literasi informasi remaja tentang bahaya merokok. Abstract: The objective of this study was to examine the effectivity of counseling with the Emo Demo method learning model on improving teenagers’ knowledge and attitude information literacy of smoking hazards. The study employseda quantitative research approach, specifically utilizing the One Group Pretest Posttest Design pre-experimental research design. The sample size for this study consists of 20 research subjects. The study was carried out at SMPN 3 Sindangkerta, located in the West Bandung Regency. The factors under investigation encompass smoking knowledge and attitudes, which will be assessed by pretest and posttest knowledge instruments, behavioral observation sheets, and counseling media utilizing the Emo Demo approach. This study focuses on the utilization of SPSS statistical software for data analysis approaches. The findings from the analysis of data on the impact of counseling on the risks associated with cigarette use, utilizing the emo-demo approach, revealed a statistically significant (p < 0.001) improvement in adolescent knowledge following counseling with the emo-demo method. This suggests that the provision of emo-demo counseling leads to enhanced knowledge among adolescents regarding the dangers of cigarette use. Similarly, the impact of counseling on the hazards associated with cigarette smoking, employing the emo-demo approach to modify attitudes towards smoking behavior, yielded a statistically significant result (Asymp Sig, 2-tailed) of 0.000, which is less than the predetermined significance level of 0.05. This finding indicates that there are discernible disparities in attitudes towards smoking behavior before and after counseling on the dangers of smoking, utilizing the emo-demo method. Therefore, it can be inferred that the utilization of the emo-demo approach in counseling sessions is efficacious in enhancing the attitudes and understanding of teenagers’ information literacy of smoking hazards.